Perancangan Analisis Risiko Bidang Administratif Departemen Impor Key Account Management PT. X - Stefani Gisella Wiratama Tong; Karina Agustin (Jurnal Titra, 2019)
Key Account Management is one of the departments owned by PT. X, whichserves as a customs broker specifically to handle VIP Customers. This research wascarried out to assist the KAM department in finding activities that could potentiallyhamper the smooth operation of the administrative import process, which could have animpact on reducing VIP Customer satisfaction. Risk analysis was carried out on all importprocesses starting from the PO Management, Import and the operational team, to theFiling division. Risk analysis is carried out using the Failure Mode and Effect Analysis(FMEA) method, and the 5 whys analysis method to find the root cause of failure of therisk findings. The results of the risk analysis show there are 64 risk findings from theentire administrative process of import. 33 risk findings in between, with a total of 25process activities, classified as priority categories and must be immediately followed up.Over all, the recommended actions for risk analysis’ result are making dashboards formonitoring shipments, training/workshops, evaluating work results, and makingstandardized documents such as procedures, work instructions, and way references.